Penyuluhan Pentingnya Akuntabilitas Pengelolaan Dana Desa - Susanto, Yohanes; Hidayat, Rian; Wardaya, Muhari Ilham; Kusumo, Haryono; Simbolon, Dasinto (Universitas Dehasen Bengkulu, 2021)
Village funds are a major focus of development and community empowerment at the local level in many developing countries. The importance of accountable village fund management is crucial as it has a direct impact on improving welfare and development at the rural level. Accountability in village fund management includes transparency, accountability, and active involvement of communities in decision-making processes related to budgets and development projects. Without strong accountability, the risk of misuse of village funds increases, resulting in waste, inappropriate use, and even corruption to the detriment of local communities. Through effective accountability mechanisms, such as transparent financial reporting and independent audits, the government and communities can ensure that village funds are used efficiently and in accordance with real needs at the village level. Accountability also plays an important role in increasing community participation in the village development process, by giving them greater access to information and enabling them to provide input and oversight on the use of village funds. The success of development programs at the village level is highly dependent on the level of accountability of village fund management. The importance of accountability in the management of village funds is also closely linked to the achievement of sustainable development goals (SDGs), particularly in addressing poverty, improving access to basic services such as education and health, and ensuring sustainable environmental protection. Countries and international donor agencies are also increasingly emphasizing the importance of accountability in the management of village funds as a condition for supporting sustainable local development. While challenges in implementing accountability in village fund management may exist, such as a lack of administrative capacity and weak oversight, steps can be taken to strengthen accountability systems, including training for village officials and the development of effective community oversight mechanisms.